PENGIMPLEMENTASIAN KITAB 1 SAMUEL 17:1-11 DALAM MEMPERSIAPKAN GENERASI UNTUK MENGHADAPI TANTANGAN ZAMAN DI SMA NEGERI 23 BATAM - Pane, Pranada; Budi, Setya; Rumaijuk, Stefan (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2025)
In the Book of 1 Samuel 17:1-11, it tells about the battle between David and Goliath. David, who was a young man with no experience in the military world, had to face Goliath and then David was able to defeat the mighty Goliath with extraordinary faith and courage. This news has deep relevance in the context of preparing the younger generation to face the challenges of the times. This article aims to explore how the principles contained in this incident can be implemented to equip future generations, especially students at State Senior High School 23, with courage, perseverance, faith and integrity in facing contemporary problems. Implementation of this teaching includes developing mental toughness, the ability to rely on God in every challenge, as well as the importance of building strong character through a clear vision of life. In addition, this article emphasizes the importance of teaching moral values, self-confidence and hard work in forming a generation that is ready to face increasingly complex global, technological and social challenges. By following David's example, the younger generation can be prepared to become individuals who are brave, responsible and have integrity in facing a future full of uncertainty.